(untitled) (gjstudies, 2019)
This research introduces a novel, cross-disciplinary framework for analyzing the relationship between accounting measurement reliability and investor risk perception by integrating principlesfrom information theory, behavioral finance, and computational linguistics. Departing fromtraditional archival methodologies that rely on historical market data and survey instruments,we develop a quantum-inspired measurement model that conceptualizes accounting reliabilitynot as a static binary property but as a probabilistic wave function collapsing upon investor observation. Our methodology employs a three-phase approach: first, we apply natural languageprocessing algorithms to analyze the linguistic uncertainty embedded in financial statementfootnotes and management discussion; second, we construct a reliability entropy index quantifying the dispersion of possible measurement outcomes; third, we utilize agent-based simulationto model how heterogeneous investors with varying cognitive architectures process this entropyto form risk assessments. We test this framework using a unique dataset comprising 1,200corporate financial reports from 1998 to 2004, manually annotated for measurement ambiguity. Our results reveal a non-linear, threshold-based relationship between measurement entropyand perceived risk, contradicting the linear assumptions prevalent in existing literature. Specifically, we identify a ’reliability illusion zone’ where moderate increases in measurement ambiguityparadoxically reduce risk perception for certain investor archetypes, a finding with significantimplications for financial regulation and disclosure standards. Furthermore, our computationalsimulations demonstrate that market stability emerges not from uniform reliability, but from adiversity of investor interpretation heuristics applied to imperfect measurements. This researchcontributes original theoretical constructs—including the Quantum Reliability Collapse postulate and the Entropy-Risk Perception Nexus—while offering a novel methodological toolkit forexamining the cognitive intermediation of accounting information.